2009
DOI: 10.1111/j.1365-2567.2008.02896.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus surface antigen impairs myeloid dendritic cell function: a possible immune escape mechanism of hepatitis B virus

Abstract: Summary Chronic hepatitis B virus (HBV) infection is the result of an inadequate immune response towards the virus. Myeloid dendritic cells (mDC) of patients with chronic HBV are impaired in their maturation and function, resulting in more tolerogenic rather than immunogenic responses, which may contribute to viral persistence. The mechanism responsible for altered mDC function remains unclear. The HBV‐infected patients display large amounts of HBV particles and viral proteins in their circulation, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
142
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(151 citation statements)
references
References 37 publications
9
142
0
Order By: Relevance
“…Regarding the mechanisms, HBsAg is the causal factor for such disruption of the pDCs, partly by upregulating suppressor molecule SOCS-1 [41]. The dysfunction of myeloid DCs (mDCs) has also been observed, presumably due to HBV particles and HBsAg [43]. The functional impairment of NK cells and DCs in chronic HBV infection might be actively involved in viral persistency.…”
Section: Nk Cells and Dcs In Chronic Hbv Infectionmentioning
confidence: 99%
“…Regarding the mechanisms, HBsAg is the causal factor for such disruption of the pDCs, partly by upregulating suppressor molecule SOCS-1 [41]. The dysfunction of myeloid DCs (mDCs) has also been observed, presumably due to HBV particles and HBsAg [43]. The functional impairment of NK cells and DCs in chronic HBV infection might be actively involved in viral persistency.…”
Section: Nk Cells and Dcs In Chronic Hbv Infectionmentioning
confidence: 99%
“…In particular, DCs control HBV recognition in vivo. Accumulating evidence has demonstrated that compared to DCs from healthy controls, DCs from patients infected with HBV exhibit impaired function [52,53] , yet the reasons for this impairment remain unclear. Researchers have focused on developing a curative DC vaccine that activates the immune response through rescuing the function of DCs to treat HBV.…”
Section: Tim-3 and Dcsmentioning
confidence: 99%
“…All of the studies report a reduction in costimulatory molecule expression following HBV exposure. 21,23,31,32 However, different antigens or virions regulated the expression of different receptors. Similarly, most studies have found cytokine production to be impaired following exposure to HBV or HBV antigens; however, similar to the phenotype experiments, different forms of the antigen had different effects (Table 4).…”
Section: Dendritic Cells In Chronic Hbv Aj Gehring and Ja D'angelomentioning
confidence: 99%